Zero budget and the element of its succession in Iraq - سدخان سناء محمد (Journal of Legal Sciences, 2019)
The budget in general is a plan of action prepared by the government and works to submit it to the legislative authority for the purpose of approval, and translates its economic and social policy into annual digital targets. In order to know the effectiveness of the public budget, it must be linked to other financial planning tools such as foreign exchange policy and credit policy and measured by the economic and social results and not only financial results. And to avoid the shortcomings that accompanied the budget because of the use of the traditional method of balancing items and finding remedies to get out of the financial crises experienced by countries in general and Iraq in particular in the unstable economic conditions. Which necessitates finding solutions and treatments to deal with these crises, the zero budget was one of the solutions and to pressure overhead and raise revenues. In addition, benefiting from the experiences of other countries that have had the lead in the application of this model of the budget, such as the United States, Japan and Europe has applied and proved successful in the industrial sectors and economic institutions since 1978. And applying this type of budget is not free of obstacles, whether administrative or legal as well as may collide with the negative treatment because of the rejection of change, but these obstacles can be overcome through the establishment of elements for the purpose of success and these components is to deal positively and seriously with this kind of budget and the construction of an integrated information system .And the provision of necessary infrastructure and the requirements and elements of its success is the gradual implementation of it and to apply it in all institutions and public utilities.